Universal low-temperature and template-free synthesis of sponge-like porous micron-sized elemental materials for high-performance lithium/potassium storage. (May 2022) - Zhu, Junlu; Liu, Xi; Wang, Wei; Liu, Zhonggang; Yue, Liguo; Zhou, Weiliang; Zhao, Ligong; Zheng, He; Wang, Jianbo; Li, Yunyong
Abstract: Interconnected porous micron-sized materials can effectively enhance the ion transfer kinetics and structural stability, thus improving their rate capability and long-term lifespan, and maintaining high volumetric performance, but developing a universal and low-temperature method for the large-scale synthesis of porous materials remains a formidable challenge. Herein, we develop a universal low-temperature and template-free strategy to fabricate a series of sponge-like, interconnected porous micron-sized elements ( e.g., Se, Te, Sb) through H2 O2 -assisted water bath. The formation mechanism of porous structure is demonstrated, originating from the non-homogeneous and continuous corrosion due to the preferential intergranular corrosion of polycrystalline particles and the soluble reaction products that do not passivate the corrosion interface. The as-obtained sponge-like porous elements present large reversible gravimetric and volumetric capacities and long stable lifespans. Specifically, the porous Te electrode delivers a high reversible capacity of 392.7 mAh g −1 (volumetric capacity: 1531.5 mAh cm −3 ) with 93.5% utilization ratio of active materials at 0.1 A g −1 and a long-stable lifespan with 500 cycles at 1.0 A g −1 in Li-Te batteries. Besides, in-situ TEM and ex-situ SEM observations demonstrate a small volume expansion and strong structural robustness of porous Te during cycling, stemming from its inward expansion mechanism and 3D stable interconnected porous structure. This work demonstrates a simple and universal strategy to design sponge-like porous materials for energy storage and catalysis, etc . Graphical Abstract: A universal, low-temperature and template-free water-bath strategy to fabricate a series of sponge-like porous elemental materials (p-Te, p-Se, and p-Sb) was developed. The formation mechanism of porous structure was also explored. Owing to the free volume, interconnected porous channel, and strong structural robustness, the porous element electrodes delivered a superior lithium/potassium storage performance and cycling stability. ga1 Highlights: A universal low-temperature and template-free strategy to fabricate sponge-like porous elements was developed. Sponge-like porous elements give high gravimetric/volumetric capacities and long stable lifespans for Li/K storage. The formation mechanism and inward expansion mechanism of porous Te were revealed. The simple and scalable method could be extended to fabricate numerous other porous materials.